Loss of NO(g) to painted surfaces and its re‐emission with indoor illumination. (25th September 2020) - Jones, Stephanie H.; Hosse, Florian P. R.; Yang, Xiaoying; Donaldson, D. James
Abstract: Heterogeneous surface reactions play a key role in the chemistry of the indoor environment because of the large indoor surface‐to‐volume ratio. The presence of photocatalytic material in indoor paints may allow photochemical reactions to occur at wavelengths of light that are present indoors. One such potential reaction is the heterogeneous photooxidation of NO to HONO. NO(g) is commonly found indoors, originating from combustion sources, ventilation and infiltration of outdoor air. We studied the interaction of NO(g) with painted surfaces illuminated with indoor fluorescent and incandescent lighting. There is a loss of NO(g) to painted surfaces in the dark at both 0 and 50% RH. At 50% RH, there is a re‐release of some of that NO(g) under illumination. The same behavior is observed for illumination of different colored paints. This is in contrast to what is seen with TiO2 as the substrate, where photoenhanced uptake of NO(g) and formation of NO2 (g) are observed. We hypothesize that the loss of NO(g) is due to adsorption and diffusion into the paint. The re‐release of NO under illumination is thought to be due to photooxidation of NO to HONO on the painted surface at higher relative humidities and subsequent HONO photolysis.